2006
DOI: 10.1128/iai.74.1.557-565.2006
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Interleukin-23 (IL-23), but Not Plasmid IL-27, Enhances the Protective Efficacy of a DNA Vaccine againstMycobacterium tuberculosisInfection

Abstract: Protection against intracellular pathogens such asTuberculosis (TB) is a global health emergency, with an estimated nine million new cases of active disease and approximately 2 million deaths per year (11a). The development of more effective vaccines than the current vaccine Mycobacterium bovis bacillus Calmette-Guérin (BCG) may improve the control of this pandemic. New approaches to the design of TB vaccines include the preparation of recombinant BCG oversecreting mycobacterial antigens (32), attenuated strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 70 publications
(71 reference statements)
1
52
1
Order By: Relevance
“…BCG antigen stimulated splenocytes from non-immunized mice (38 +/− 17 pg/mL) had similar level of IL-1β compared to mice immunized with BCG/ lactoferrin (44 +/− 21 pg/mL); production of IL-1β was significantly decreased in splenocytes from the BCG immunized group (24 +/− 13 pg/mL) compared to the BCG/lactoferrin group. TB vaccines are useful when given as a one time injection or when administered using various schedules of prime-boost protocols [10,14,15,[43][44][45][46][47][48][49]. The next experiments examined the BCG/lactoferrin saline immunization protocol to generate protection against MTB infection when mice were immunized once (Protocol C), or when boosted prior to infection (Protocol D).…”
Section: Resultsmentioning
confidence: 99%
“…BCG antigen stimulated splenocytes from non-immunized mice (38 +/− 17 pg/mL) had similar level of IL-1β compared to mice immunized with BCG/ lactoferrin (44 +/− 21 pg/mL); production of IL-1β was significantly decreased in splenocytes from the BCG immunized group (24 +/− 13 pg/mL) compared to the BCG/lactoferrin group. TB vaccines are useful when given as a one time injection or when administered using various schedules of prime-boost protocols [10,14,15,[43][44][45][46][47][48][49]. The next experiments examined the BCG/lactoferrin saline immunization protocol to generate protection against MTB infection when mice were immunized once (Protocol C), or when boosted prior to infection (Protocol D).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that IL-23 was not essential for the development of resistance during the acute stage of infection. By contrast, during immunization with a DNA vaccine expressing Ag 85B (DNA85B), plasmid-expressing IL-23 was as effective as plasmid IL-12 as an adjuvant to increase the frequency of IFN-␥-secreting T cells and protection against aerosol M. tuberculosis infection (23).…”
Section: P Rotective Immunity Against Mycobacterium Tuberculosismentioning
confidence: 99%
“…The blunt ends were self-ligated to yield IL-12p40 and the sequence integrity confirmed. The bioactivity of plasmids expressing IL-12 or IL-23 was confirmed previously (23,25). The DNA used in immunizations was prepared by equilibrium centrifugation in a continuous CsCl-ethidium bromide gradient.…”
Section: Preparation Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow progenitor cells were generated as previously described (30). For in vitro studies, rBCG strains were grown in 7H9 broth supplemented with 10% ADC (without albumin) for 14 days.…”
Section: Apc Preparation and Ag Presentationmentioning
confidence: 99%